Exploring EFL Students’ Challenges in Writing Descriptive Texts: A Case Study of Junior High School Learners in Cimahi - Muman, Muman; Rahayu, Destria (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing is a key component of English language learning. This study aimed to explore the difficulties faced by junior high school students in writing descriptive texts in English and to identify the linguistic aspects that hinder their performance. In this study, the researchers used a qualitative case study design which involved 36 seventh-grade students from SMPN 8 Cimahi as the research subjects. The findings revealed that students performed best in content (26.89%), indicating that they were able to stay on topic and generate relevant ideas. In contrast, the lowest scores were found in grammar (16.61%) and mechanics (17.99%), reflecting frequent errors in tense use, subject–verb agreement, punctuation, and capitalization. Interviews further found that limited vocabulary, low writing confidence, and difficulty in idea organization were major obstacles. Despite these challenges, students showed positive attitudes toward learning English and were more motivated when engaging in fun and interactive learning activities, such as games and outdoor tasks. These findings suggest that integrating vocabulary-building activities and communicative grammar practice into writing instruction can help students enhance their descriptive writing skills.